2016
DOI: 10.5585/remark.v15i3.3218
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Sustainable Consumption

Abstract: Currently, environmental sustainability is the subject of many discussions, both in biology and ecology and also in economy. The results of these discussions are shown in international forums promoted by governments, programs of social and environmental responsibility carried out by companies, and sustainable consumption initiatives adopted by consumers trying to make a difference through their consumption. This study analyzes the sustainable consumption phenomenon, from the consumer point of view, investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
3
10
0
3
Order By: Relevance
“…A previous study has identified that personality characteristics are considered to be external variables and assumed to influence intention toward a given behavior indirectly mediated by the components of TPB (Ajzen and Fishbein, 1980). For example, Ribeiro et al (2016) confirmed the positive influence of personality traits on sustainable consumption. More specifically, the positive relationship between fashion leadership and attitude toward the environments has been confirmed (Cho and Workman, 2014), indicating that consumers with high levels of fashion leadership might be more likely to participate in sustainable behavior.…”
Section: The Influence Of Fashion Leadershipmentioning
confidence: 73%
“…A previous study has identified that personality characteristics are considered to be external variables and assumed to influence intention toward a given behavior indirectly mediated by the components of TPB (Ajzen and Fishbein, 1980). For example, Ribeiro et al (2016) confirmed the positive influence of personality traits on sustainable consumption. More specifically, the positive relationship between fashion leadership and attitude toward the environments has been confirmed (Cho and Workman, 2014), indicating that consumers with high levels of fashion leadership might be more likely to participate in sustainable behavior.…”
Section: The Influence Of Fashion Leadershipmentioning
confidence: 73%
“…Personality traits refer to factors reflecting individual characteristic patterns of thoughts as well as feelings and further reflecting individual behavioral patterns [13]. Personality traits might influence one's attitude towards PEBs [14][15][16], and then further contribute to sustainable intentions and behaviors directly or indirectly [17,18]. Some studies support that people with some specific personality characteristics (so-called "green personalities") tend to present stronger attitudes towards PEBs and have more environmental protection potential [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dahl (1998) pointed out that sustainable consumption refers to the need to stay within the global sustainability of resources. Ribeiro, Veiga & Higuchi (2016) added the search for ecologically-correct products and services, the preference for corporations and organizations actively engaged in environment conservation, the saving of resources such as water and energy, the using of materials and equipment up to the end of its life service, the reusing, whenever possible, the right destination of residuals to recycling and the propensity to a lifestyle with a smaller negative environmental impact.…”
Section: Literature Review 21 Sustainable Consumptionmentioning
confidence: 99%